Religiusitas, Pola Asuh Otoriter dan Perilaku Prososial Remaja di Pondok Pesantren - Eka Putri, Ellyana Ilsan; Noviekayati, IGAA (Persona:Jurnal Psikologi Indonesia, 2015)
The purpose of this research is testing the relation between religiousnessand authoritarian parenting with prosocial behavior of adolescents in Islamicbuilding school. The subjects of this research are 119 teenagers, 14-17 years. Thisresearch uses quantitative method. The data collection method uses the scale ofpsychology are arranged based on variable construct theory of religiousness,authoritarian parenting and prosocial behavior. The data analysis used isregression and partial analysis. Research result indicates there is a relation betweenreligiousness and the more authoritarian parenting with prosocial behavior (Freg=0,7758; p = 0,001 <0,01), while partially found that no relation betweenreligiousness to prosocial behavior (rpartialPENDAHULUANIndonesia beberapa tahun terakhir inidihadapkan pada kenyataan akan beragamkonflik. Beberapa contoh konflik yang tampakdan langsung dapat dirasakan adalah keacuhan,ketidakpedulian, dan permusuhan. Pelakubukan hanya masya-rakat awam, namun jugapelajar yang masih berusia remaja. Remaja233= 0,94; treg= 0,803 ; p = 0,425>0,05),and there is a negative relationship between the more authoritarian parenting withprosocial behavior (rpartial= -0,395; treg= -3,644; p = 0,001<0,01).Keywords : prosocial behavior, religiousness, authoritarian parenting, adolescent